Interaction between early life stress and alcohol dependence on neural stress reactivity. (7th March 2014) - Yang, Hongyu; Spence, Jeffrey S.; Briggs, Richard W.; Rao, Uma; North, Carol; Devous, Michael D.; Xiao, Hong; Adinoff, Bryon
Abstract Stress response biologic systems are altered in alcohol‐dependent individuals. Early life stress (ELS) is associated with a heightened risk of alcohol dependence, presumably because of stress‐induced neuroplastic changes. This study was designed to assess the contribution of ELS to a stress‐induced neural response in alcohol‐dependent participants. Fifteen alcohol‐dependent men abstinent for 3–5 weeks and 15 age‐ and race‐matched healthy controls were studied. Anticipatory anxiety was induced by a conditioned stimulus paired with an uncertain physically painful unconditioned stressor. Neural response was assessed with functional magnetic resonance imaging. ELS was assessed with the Childhood Adversity Interview. There was a significant interaction between ELS and group on blood‐oxygen‐level‐dependent (BOLD) amplitude during anticipatory anxiety in the right amygdala and bilateral orbitofrontal cortex, posterior putamen and insula. Higher ELS scores were associated with decreased BOLD amplitude during anticipatory anxiety in alcohol‐dependent, but not control, participants. These findings suggest that ELS interacts with alcohol dependence to induce a muted cortico‐striatal response to high threat stimuli. Allostatic changes due to both ELS and excessive alcohol use may jointly induce persistent changes in the neural response to acute stressors.